Toxic Chemical Governance Failure in the United States: Key Lessons and Paths Forward. (10th July 2019) - Chiapella, Ariana M; Grabowski, Zbigniew J; Rozance, Mary Ann; Denton, Ashlie D; Alattar, Manar A; Granek, Elise F
Abstract: Over 40 years of regulations in the United States have failed to protect human and environmental health. We contend that these failures result from the flawed governance over the continued production, use, and disposal of toxic chemicals. To address this failure, we need to identify the broader social, political, and technological processes producing, knowing, and regulating toxic chemicals, collectively referred to as toxic chemical governance. To do so, we create a conceptual framework covering five key domains of governance: knowledge production, policy design, monitoring and enforcement, evaluation, and adjudication. Within each domain, social actors of varying power negotiate what constitutes acceptable risk, creating longer-term path dependencies in how they are addressed (or not). Using existing literature and five case studies, we discuss four paths for improving governance: evolving paradigms of harm, addressing bias in the knowledge base, making governance more equitable, and overcoming path dependency.